2019
DOI: 10.1055/a-0959-2113
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes Towards Concussion in Western Province Rugby Union Senior Club Rugby Players

Abstract: Concussion is a frequently occurring injury in rugby which is not usually reported to coaches or medical staff. Recognition and treatment of concussion should be a priority; however, education surrounding concussion knowledge and attitudes of the players have been lacking. The aim of this study was to investigate the knowledge and attitudes toward concussion in Western Province Rugby Union (WPRU) Super League senior club rugby players. This study focused on gathering quantitative information from WPRU club rug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
3
7
0
Order By: Relevance
“…The study from 2016 also found similar attitudes in surveyed coaches and medical professionals, indicating that this is not just a player issue and highlighting the importance of concussion education from rugby-governing bodies. Most negative attitudes toward concussion reporting were related to feeling a responsibility to play, especially in important matches, 22,28 and previous studies have indicated a culture of playing injured for a multitude of reasons, 16,29 similar to our findings. It should be noted that some surveys have reported sufficient knowledge of a concussion and its risks in certain groups, 28 but given the misconceptions that many athletes maintain about the concussion risk, athlete education remains an important method of management for this injury.…”
Section: Discussionsupporting
confidence: 90%
“…The study from 2016 also found similar attitudes in surveyed coaches and medical professionals, indicating that this is not just a player issue and highlighting the importance of concussion education from rugby-governing bodies. Most negative attitudes toward concussion reporting were related to feeling a responsibility to play, especially in important matches, 22,28 and previous studies have indicated a culture of playing injured for a multitude of reasons, 16,29 similar to our findings. It should be noted that some surveys have reported sufficient knowledge of a concussion and its risks in certain groups, 28 but given the misconceptions that many athletes maintain about the concussion risk, athlete education remains an important method of management for this injury.…”
Section: Discussionsupporting
confidence: 90%
“…The current study found that approximately 80% of participants answered all CKI items correctly. This is (1) comparable to the findings from three prior US studies of physical education teachers, collegiate athletes and football coaches (eg, 82%27–29) and (2) higher than reported in studies of contact-sport athletes in the UK and South Africa (eg, 66%,19 67%,30 70%31); all of whom could be expected to be more knowledgeable about concussion than members of the general public. This could indicate that this study has a sample bias (eg, the volunteers were particularly interested in concussion).…”
Section: Discussionsupporting
confidence: 81%
“…This is consistent with previous research in which the recognized symptoms were also only two out of eight. 23 The other symptoms, which were often selected, were dizziness (86%), difficulty remembering (72%) and drowsiness (70%). Significant differences were found between the stakeholders for the following symptoms: difficulty speaking (p < 0.01), sensitivity to light (p = 0.01), difficulty remembering (p < 0.01), drowsiness (p < 0.01), feeling in a fog (p = .0.02), difficulty concentrating (p = 0.01) and dizziness (p = 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…10 Kraak et al. 23 investigated the abovementioned population and found that players scored 67% for concussion knowledge and 62% for concussion attitude. Previous research indicated that 65 to 70% was deemed a moderate level of knowledge and attitude, whereas above 75% was considered sufficient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation